Smart home automation with Linux - Goodwin, Steven, 1973- (New York : Apress, 2010)
"With this book you will turn your house into a smart and automated home. You will learn how to put together all the hardware and software needed for home automation, to control appliances such as your teakettle, CCTV, light switches, and TV...In the realm of media and media control, for instance, you'll learn how you can read TV schedules digitally and use them to program video remotely through email, SMS, or a web page...You'll also learn techniques for streaming music and video from one machine to another, how to give your home its own Twitter and e-mail accounts for sending automatic status reports, and the ability to remotely control the home lights or heating system..."--P. [4] of cover.
Appliance control -- Appliance hacking -- Media systems -- Home is home -- Communication -- Data sources -- Control hubs.
Includes index.
"Learn how to control your home from your PC"--P. [1] of cover.
Keywords: Linux; Home automation; Home automation -- Handbooks, manuals, etc